El control de armas ligeras y de pequeño calibre (salw) como contribución para establecer la seguridad en sociedades posconflicto - Smith, Henri (Revista Española de Desarrollo y Cooperación, 2023)
This paper begins with a short introduction to the issue of SALW control. It then establishes key relationships between security-building, broader peace-building activities and SALW control, before suggesting practical ways in which integration and coordination could help to achieve greater collective impact on reducing insecurity, tackling violent conflict, and encouraging development.